Proekologiczne i prooszczędnościowe zachowania gospodarstw domowych jako konsumentów energii - Ropuszyńska-Surma, Edyta; Węglarz, Magdalena (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The aim of the article is to indicate the changes related to households’ behavior linked to energy saving and pro-ecological activities. Therefore, the authors conducted a comparison analysis of the results of the nationwide Polish research about Polish ecological awareness and identified — as part of the Polish National Science Centre (NCN) project called “Modelling prosumers’ behavior on the energy market” — pro-economical attitudes of households. The first part of this paper presents the opinions of Poles about the possibilities of development of the different kinds of energy sources in Poland, taking into special consideration the development of renewable energy sources. In the second part of this paper the authors describe households’ behavior connected with saving energy. They analyzed pro-economical behavior such as: switching off lights in empty rooms, unplugging phone chargers after use, using economical bulbs and unplugging devices that are not in use. The diversifying variables of behavior are: sex, age, income. The analysis of households’ behavior was supplemented with the analysis of pro-economical attitudes of Wroclaw University students
Keywords: ecological awareness; prosumer; consumer; air pollution